Archetypal Grief - Brewster, Fanny, author.
1 online resource (174 pages)
Keywords: Archetypal Grief: Slavery’s Legacy of Intergenerational Child Loss is a powerful exploration of the intergenerational psychological effects of child loss as experienced by women held in slavery in the Americas and of its ongoing effects in contemporary society. It presents the concept of archetypal grief in African American women: cultural trauma so deeply wounding that it spans generations. Calling on Jungian psychology as well as neuroscience and attachment theory, Fanny Brewster explores the psychological lives of enslaved women using their own narratives and those of their descendants, and discusses the stories of mothering slaves with reference to their physical and emotional experiences. The broader context of slavery and the conditions leading to the development of archetypal grief are examined, with topics including the visibility/invisibility of the African female body, the archetype of the mother, stereotypes about black women, and the significance of rites of passage. The discussion is placed in the context of contemporary America and the economic, educational, spiritual and political legacy of slavery. Archetypal Grief will be an important work for academics and students of Jungian and post-Jungian studies, archetypal and depth psychology, archetypal studies, feminine psychology, women’s studies, the history of slavery, African American history, African diaspora studies and sociology. It will also be of interest to analytical psychologists and Jungian psychotherapists in practice and in training.